EFFORTS TO IMPROVE DISCIPLINE OF SERVICE SERVICES ON THE BRIDGE FOR LIFE SAFETY ON THE MV.HTC CHARLIE SHIP - Sijabat, Panderaja; Rochman, Abdul; Dion Octovianus, Steven (Dinasti Publisher, 2021)
Mualim has an important role in carrying out ship movement while sailing for the safety of all crew members. In this case the officer has the responsibility to carry out guard duty on the bridge. This study aims to further increase knowledge about the importance of discipline in carrying out guard services on the bridge and to carry out guarding procedures in accordance with established procedures, especially when changing guard (handing over). This research was carried out on board the MV. HTC CHARLIE which is one of the ships owned by PT. INTERGIS. Implementation during the author's practice of the Sea (Prala), so that the source of the data obtained directly from the place of doing research in the form of information based on observations and interviews with the officer in charge. This study shows that there are still shortcomings in carrying out the duty of duty in accordance with the procedures and the lack of discipline of the missionary when on guard duty. By conducting this research, it is possible to make an overview of the watch service in accordance with the procedures for handing over the guard and the importance of discipline in carrying out the watch service on the bridge.